Offset ratios and temporary contract designs for climate integrity in carbon farming - Lötjönen, Sanna; Kulovesi, Kati; Lång, Kristiina; Ollikainen, Markku (Taylor & Francis, 2024)
In this study, we examine how to enhance the climate integrity of carbon credits from carbon farming practices. The key requirements for climate integrity include permanence, additionality, and measurement and verification. Farmers are typically willing to make carbon contracts for a finite time only in voluntary markets or with the government and receive carbon credits to sell as offsets. This contradicts the requirement of the permanence of carbon sequestered in soils. To solve this problem and to facilitate greater participation by farmers in carbon sequestration, we show how temporary contracts can be made to address the issue of permanence by using offset ratios. The notion of the offset ratio refers to the share of one emission unit that one unit of temporary sequestered carbon replaces. Thus, the offset ratio transforms temporary sequestration to permanent emissions reductions. We propose the use of a discounting method to calculate the offset ratio. The ratio varies with the carbon contract length, employed discount rate, and assumptions about the evolution of the soil carbon stock. We apply this approach to cultivating catch crops for carbon sequestration on a north‒south gradient in Finland, Denmark, and France. We show that the offset ratio approach works well for every selected country. Carbon farming contracts are profitable for farmers provided that revenue under the contract exceeds that in the baseline. Profitability is highly dependent on catch crop cost, annual increase in soil carbon, and the discount rate. We apply offset ratios to assess the climate integrity of some existing crediting programs and find that the discounting method yields a lower offset ratio in almost all cases yielding a lower number of credits than launched in these programs.
Keywords: carbon farming; carbon credit; offset ratio; permanence; discounting method